1998
DOI: 10.1002/(sici)1096-9101(1998)22:4<228::aid-lsm8>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Acute results, complications, and effect of lesion characteristics on outcome with the solid‐state, pulsed‐wave, mid‐infrared laser angioplasty system: Final multicenter registry report

Abstract: Background and Objective:The solid-state, mid-infrared holmium:YAG laser (2.1 m wavelength) is a relatively new percutaneous device that has recently been evaluated in a multicenter study. Because of its unique wavelength and photoacoustic effects on atherosclerotic plaques, this laser may be useful in treatment of symptomatic patients with coronary artery disease. This study sought to evaluate the safety and efficacy of mid-infrared laser angioplasty in the treatment of coronary artery lesions. occurred in 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In the present study, based on our previous serial studies, the optimal conditions for endovascular laser intervention by Argon laser were an output power and exposure time of 6 W in output and 3 s, respectively, for the bare laser fiber, and a tip temperature and exposure time of 200°C and 5 sec, respectively, for the heated tip. 2,16) On the other hand, several other sets of laser parameters (6-12 W output, 3-10 s irradiation time) have been reported depending on to the kind of laser system and laser fibers used.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] In the present study, based on our previous serial studies, the optimal conditions for endovascular laser intervention by Argon laser were an output power and exposure time of 6 W in output and 3 s, respectively, for the bare laser fiber, and a tip temperature and exposure time of 200°C and 5 sec, respectively, for the heated tip. 2,16) On the other hand, several other sets of laser parameters (6-12 W output, 3-10 s irradiation time) have been reported depending on to the kind of laser system and laser fibers used.…”
Section: Discussionmentioning
confidence: 88%
“…The presence of thrombus in the lesion has been reported to increase the success of angioplasty treatment using holmium laser, 18 while an earlier study using excimer laser found that it increased distal embolization and non-Q wave MI related to the procedure. 19 Topaz and associates, 4 applying ELCA in 50 patients with acute MI, obtained a success rate of laser ablation of 98% and of the procedure of 100%.…”
Section: Discussionmentioning
confidence: 98%
“…temperatures required for peripheral artery recanalization in patients using LTA were found to range between 74-4508C at the probe tip. Thus, a wide range in temperatures generated by lasing and various devices may explain the great differences in the incidence of restenosis observed in clinical studies [21,22]. In fact, Spears et al [23] using laser balloon angioplasty demonstrated that different energy levels altered the restenosis rate in human coronary arteries.…”
Section: Discussionmentioning
confidence: 99%